Cystic fibrosis autoantibody signatures associate with Staphylococcus aureus lung infection or cystic fibrosis-related diabetes - Yadav, Ruchi; Li, Quan-Zhen; Huang, Hanwen; Bridges, S. Louis; Kahlenberg, J. Michelle; Stecenko, Arlene A.; Rada, Balázs (Frontiers in Immunology, 2023)
Introduction While cystic fibrosis (CF) lung disease is characterized by persistent inflammation and infections and chronic inflammatory diseases are often accompanied by autoimmunity, autoimmune reactivity in CF has not been studied in depth. Methods In this work we undertook an unbiased approach to explore the systemic autoantibody repertoire in CF using autoantibody microarrays. Results and discussion Our results show higher levels of several new autoantibodies in the blood of people with CF (PwCF) compared to control subjects. Some of these are IgA autoantibodies targeting neutrophil components or autoantigens linked to neutrophil-mediated tissue damage in CF. We also found that people with CF with higher systemic IgM autoantibody levels have lower prevalence of S. aureus infection. On the other hand, IgM autoantibody levels in S. aureus-infected PwCF correlate with lung disease severity. Diabetic PwCF have significantly higher levels of IgA autoantibodies in their circulation compared to nondiabetic PwCF and several of their IgM autoantibodies associate with worse lung disease. In contrast, in nondiabetic PwCF blood levels of IgA autoantibodies correlate with lung disease. We have also identified other autoantibodies in CF that associate with P. aeruginosa airway infection. In summary, we have identified several new autoantibodies and associations of autoantibody signatures with specific clinical features in CF.